Hubungan Peran Bidan dan Dukungan Suami terhadap Pemilihan Kontrasepsi Implan - Jayanti, Ira; Ayu Dwi Lismawaty M, Ida; Rahmat Hidayat, Anas (Pusat Kajian dan Pengelola Jurnal FKM UMI, 2025)
Implant contraception is one of the long-term contraceptive methods (Long-Term Contraceptive Method/MKJP) that is effective in preventing pregnancy. This study aims to analyze the relationship between the role of midwives and husbands' support for the choice of implant contraception in the Kotabaru Regency area. This study is a quantitative study with a cross-sectional research design. The population in this study were 1,718 fertile age couples who used contraception at Pantai Health Center. In this study, the sampling technique used was a purposive sampling technique to select individuals who met the research criteria with a sample size of 315 people who met the criteria as samples. Based on the results obtained, there is a relationship between husbands' support and the choice of implants in the Kotabaru Regency area. The results of the chi-square test yielded a p-value of 0.001 (p < 0.05), indicating a significant relationship between the role of midwives and the choice of implants in the Kotabaru Regency area. The statistically significant relationship underscores the importance of integrating midwives' roles and family support into reproductive health strategies, which can influence contraceptive choices effectively